THE EFFECT OF VAPOR PRESSURE ON THE RATE OF ISOTOPIC EXCHANGE BETWEEN WATER AND WATER VAPOR - Ingraham N.L.; Criss R.E. (My University, 1998)
Experimental determination of the rate of isotopic exchange between water and water vapor indicates a dependence on temperature. In these experiments, two beakers that initially contained waters with differing isotopic compositions were allowed to exchange in sealed boxes at different temperatures. Over time, the two waters exponentially approach common D/H and 18O/16O ratios, with the exchange and isotopic transport being effected via the vapor phase. The rate constant (k') at 21°C was found to be 0.15 cm/day, a value that basically confirms the results of Ingraham and Criss [Ingraham, N.L., Criss, R.E., 1993. The effects of surface water area and volume on the rate of isotopic exchange between water and water vapor. J. Geophys. Res. Atmos. 98 (D11) 20547-20553.] of k'=0.12 to 0.18 cm/day at ambient temperatures (~20°C). However, new experiments at 52°C indicate a fivefold increase in the rate constant, which is 0.82 cm/day. The ratio of the 52°C and 21°C rate constants (0.82/0.15) is identical within error to the ratio of the saturation vapor pressures (102.09/18.65) at the respective temperatures. Our theoretical prediction of a linear relationship between the isotopic exchange rate and the vapor pressure is confirmed by our experimental relationship, k'cm/day=0.00803*v.p., where the vapor pressure is in torr. This relationship allows the separation of the effects of isotopic exchange from those of evaporation into unsaturated atmospheres.
Keywords: VAPOR PRESSURE; ISOTOPIC EXCHANGE; WATER; WATER VAPOR